NUTRITION AWARENESS THROUGH ENGLISH BLENDED LEARNING FOR NURSING STUDENTS IN THE CONTEXT OF HEALTH TOURISM EDUCATION - Si Putu Agung Ayu Pertiwi Dewi; Ni Komang Purwaningsih (Politeknik Pariwisata Makassar, 2025)
This study explores the integration of English blended learning in enhancing nutrition awareness among nursing students within the context of health tourism education in Bali. With the growing demand for healthcare professionals who are both linguistically competent and nutritionally literate, this research investigates how a hybrid approach to English for Specific Purposes (ESP) can simultaneously improve language skills and health education outcomes. A qualitative descriptive design was employed, analyzing essay responses from 14 nursing students at STIKES Bina Usada Bali through thematic content analysis. The findings reveal three major themes: (1) the perceived importance of English proficiency in accessing global nutrition knowledge and patient communication, (2) challenges in traditional language learning methods, including limited speaking practice and contextual relevance, and (3) strong student support for blended learning models combining online modules with interactive classroom sessions. Students emphasized that integrating nutrition topics into English instruction increased their engagement and awareness of dietary health, particularly in serving international health tourists. The study concludes that blended learning is a viable and effective strategy for achieving dual educational goals, language development, and nutrition literacy. It recommends the development of a structured ESP curriculum focused on health tourism, incorporating asynchronous video lessons, real-world case studies, and peer discussions. This approach aligns with national education affirmations and supports the cultivation of globally competent nursing graduates ready for Bali’s evolving health and hospitality landscape.